Efficiency of group work in harvesting mountainous broadleaf thinning stands - Zečić, Željko (Zbornik gozdarstva in lesarstva, 2004)
Group work was researched for felling, processing, skidding and quality inspection activities in mountainous broadleaf thinning stands with approximately the same terrain and stand conditions. The stands were 55 and 70years old. In the forest communities of the mountainous beech forest with dead nettle (Lamio orvale - Fagetum sylvaticae/Ht. 1938) and the forests of the sessile oak and horn beam with beech (Epimedio - Carpinetum betuli var. Fagus sylvatica/Ht. 1938/Borth.1963), the main tree species are beech and sessile oak with the addition of other broadleaf species. Productivity was examined in two groups. The first comprised of five workers (A) and the secondof four workers (B). The first group was equipped with two tractors and three chain saws while the second used two tractors and two chain saws as wellas other necessary equipment. The effective time of the cutters spent on felling ranged from 36 to 42.9%, finishing and measurement took up 21%, while the effective time for the tractors ranged from 42.4 to 59%. The effective time per tree ranged from 3.62 to 3.77 minutes, i.e. from 8.46 min/m3 to 12.91min/m3 per unit. The daily output achieved by the Ecotrac and Torpedo tractors at a distance of 300 meters was 20.77.m3/day for group A, while the optimised output was 67.02 m3/day. The output achieved by both tractors in group B was 17.25 m3/day while the optimised output was 30.72 m3/day. The average performance per worker in group A was 4.15.m3/day while the optimised performance was 8.38 m3/day. For group B the average performance per worker was 4.31.m3/day and the optimised performance was 7.68 m3/day. The optimisation of the groups lowered the unit cost of production (300 m distance) for group A from 21.36 EUR/m3 to 6.62 EUR/m3, and for group B from 22.09 EUR/m3 to 12.41 EUR/m3.
Keywords: forestry; gozdarstvo; redčenje; stroški dela